PRIVACY-PRESERVING REAL TIME TRACING SYSTEM FOR COVID-19 PATIENT USING GPS TECHNOLOGY - Azizah, Nuril Lutvi; Indahyanti, Uce (PATTIMURA UNIVERSITY, 2022)
The new normal condition in Indonesia does not mean that Indonesia is completely free from infection with the Covid 19 virus. Individuals exposed to the Covid 19 virus have symptoms like mild, moderate, to severe condition. Most individuals who have mild symptoms are self isolating at their home until tested negative for the Covid 19 virus. The impact of Covid 19 has led to an increase in the use of gadgets to access all the information needed. The purpose of this study is to provide information regarding patients infected with Covid 19 in a certain area through a tracing application. The application can help public to find out how many individuals are infected with Covid 19 in the surrounding environment by prioritizing privacy-preserving in a real time. The method used in this study is a combination of graph theory and GPS tracing system on a gadget. The initial stage of this study was carried out through tracing Covid 19 patients based on their position of residence. The final stage of the study was carried out using a graph approach based on distance and percentage of transmission. The result of this study obtained privacy-preserving real-time tracing with the predicted precentage of Covid 19 transmission susceptibility within the scope of danger or vulnerability, quite safe, and secure. Furthermore, individuals can take precautions by maintaining a safe distance.